The disease and economic burden of notified and underestimated Campylobacter enteritis cases and associated sequelae in Germany - Elisabeth Schorling; Sonja Lick; Bettina Rosner; Sebastian Knorr; Hendrik Wilking; Pablo Steinberg; Dagmar Adeline Brüggemann (PLoS ONE, 2025)
Background According to surveillance data, Campylobacter enteritis (CE) has been the most frequently notified bacterial gastrointestinal disease in Germany and Europe for many years. Presumably, the total number of cases is underestimated because an unknown number of cases is not diagnosed and some diagnosed cases are not reported in the surveillance system. The aim of this study was to estimate the disease and economic burden of CE and its related sequelae in Germany. Methods The disability-adjusted life years (DALY) as well as the direct and indirect costs associated with the five-year (2018–2022) mean number of CE cases and related sequelae were estimated in a Monte Carlo simulation. The age- and gender-specific characteristics were integrated where possible. The underestimated CE cases were quantified by reconstructing the surveillance pyramid using age group-specific health care seeking parameters. Results The estimated incidence rate was 553 CE cases (95%-CI: 551–555 cases) per 100,000 inhabitants per year. This corresponds to 7.7 underestimated cases per notified case. Underestimation was lowest in the age group <5 years and highest in the age group 15–29 years. The notified plus underestimated CE cases and associated sequelae resulted in a loss of 6,764 DALY (95%-CI: 6,689-6,839 DALY), 88% of which were due to sequelae. The total economic burden amounted to 263.5 million Euros (95%-CI: 262.5–264.4 million Euros). Approximately 25% of the total DALY and costs were attributable to the notified cases. Conclusions The results suggest a substantial burden due to CE, both in terms of DALY and costs, in Germany. Especially the high number of underestimated cases and associated sequelae contribute to the health and economic burden – although some remaining uncertainties cannot be ruled out. By using age-specific multipliers to determine the underestimated cases, age-related differences in DALY and cost of illness can be accounted for, thereby preventing an overestimation of the total burden.